Social immunity can be a consequence and cause of social evolution - Ming Liu; Thomas W. Scott; George Shillcock; Christopher D. Pull; Stuart A. West (Proceedings of the National Academy of Sciences, 2026)
Many social insects respond to pathogens in ways that reduce pathogen transmission within their social groups, with behaviors such as grooming or removing infected individuals. This “social immunity” within a group has been compared to the immune response of multicellular organisms. However, we lack a theoretical framework for understanding both the possible evolutionary origins and consequences of social immunity. How restrictive are the conditions for the initial evolution of social immunity? Would we expect social immunity to influence or even coevolve with other aspects of social complexity, such as colony size or the number of castes? We developed a theoretical framework for examining the evolutionary scenarios that may link social immunity and social evolution. We found that: (1) social immunity can be favored in relatively simple social systems, where relatedness between group members can vary; (2) social immunity can coevolve with the age of colony maturation, leading to colonies that grow for a longer period before they start reproducing; and (3) social immunity often leads to the evolution of larger colonies, which can then select for more worker castes. These results suggest that social immunity can be both a consequence and a cause of social evolution.